Paham Multikulturalisme Masyarakat Minangkabau Hari ini: Analisis Konflik dalam Teks Novel Sitti Nurbaya (Kasih Tak Sampai) karya Marah Rusli - Auzi Ilaturahmi (Jurnal Bahasa dan Sastra, 2021)
The map of Indonesian literature has always been dominated by the Minang people. It is no wonder that portraits of Minangkabau people are easily recognizable because they are reflected in the great works of their writers. For example, Sitti Nurbaja's romance, Mistakes in Upbringing, Drought, People of Blanti, and Tangled. In this phenomenal work, what is interesting is the understanding of multiculturalism surrounding the development of the storyline. It marks that multiculturalism has become a national problem that must be solved and fought for. What needs to be questioned is whether the multicultural idea has been successfully fought for so that multicultural conflicts are no longer visible in Minangkabau society today. Therefore, this study aims to describe the responses of the characters contained in the novel. Then, the social reality contained in the text is further described and analyzed to then be compared with the conditions of Minangkabau society today. To realize this goal, this study incorporates the theory of sociology of literature which is supported by the theory of conflict and integration as well as semiotics with the heuristic reading method. The term multicultural refers to cultural diversity. In this diversity, cultural phenomena are certainly not free from conflicts as a result of the intersection of different cultures. Furthermore, integration is used as a solution to resolve conflicts that occur. Therefore, this type of descriptive qualitative research is used. From the results of the study, researchers have found no more dimensions of multiculturalism such as (1) the dimension of conflict which is the root of the emergence of multiculturalism, (2) the dimension of liberating oneself from the culture of seclusion, (3) the dimension of manifesting the status of sutan or high-ranking people who may have multiple wives. , (4) dimensions of manifesting the status of sutan or high-ranking people who do not have the obligation to provide for their wives and children, (5) dimensions of eradicating how to treat wives as slaves, and (6) dimensions of gender equality.